Peran Teknologi dalam Mengurangi Pajak di Era Digital - Herfita Ayu Nayla; Clara Oktaviana; Desriana, Kurniawati Dwi (Cattleya Darmaya Fortuna, 2025)
Tax evasion is an illegal act committed by taxpayers to reduce the amount of tax payment that should be paid according to the prevailing laws and regulations. This act may involve document forgery, inaccurate data reporting, failure to report income, false expense claims, and the use of fake tax invoices. Tax evasion reflects a disregard for formal tax obligations by parties who are supposed to comply with the national tax system. This study aims to describe and analyze the role of information technology in minimizing tax evasion practices in the digital era. Using a descriptive qualitative approach, this study explores how information technology can enhance transparency, efficiency, and accuracy within the tax system and strengthen oversight of taxpayer behavior.